Strategi Guru dalam Mengatasi Kesulitan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII Sipakabaji di SMP Negeri No. 18 Kecamatan Lau Kabupaten Maros - Abu Bakar, Amalia Ramahdani; Abu Baedah, Said Syarifuddin; Wahab, Abdul; Mustamin, Mustamin; Juhri, Juhri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This qualitative study investigated the strategies implemented by Islamic Religious Education teachers in overcoming learning difficulties of class VIII Sipakabaji students at SMP Negeri 18 Lau Maros, Maros Regency. The results of the study showed several factors causing students' learning difficulties, including lack of interest and motivation to learn, low concentration in class, lack of discipline in learning, and lack of parental support for children's learning achievements. This condition is not experienced by all students equally, but it is a challenge for teachers in creating effective learning. Cultivating students' interest in reading is also an obstacle, considering the strong influence of social media among teenagers. The strategies implemented by teachers to overcome students' learning difficulties include individual approaches, providing motivation, and tutoring. Teachers try to give special attention to each student according to their individual needs and learning difficulties. Motivation is given consistently to increase students' enthusiasm for learning and self-confidence. Tutoring is carried out both inside and outside class hours to help students understand difficult subject matter. In addition, teachers also emphasize mastery of learning materials in accordance with the syllabus and Learning Implementation Plan (RPP). The delivery of material is carried out systematically and interestingly so that students can more easily understand and remember the material. Teachers also try to create a conducive and enjoyable learning atmosphere to increase student participation and enthusiasm in participating in learning.